A simplified LC-MS/MS method for the quantification of the cardiovascular disease biomarker trimethylamine-N-oxide and its precursors - Katharina Rox; Silke Rath; Dietmar H. Pieper; Marius Vital; Mark Brönstrup (Elsevier, 2021)
Trimethylamine-N-oxide (TMAO) has emerged as a potential biomarker for atherosclerosis and the development of cardiovascular diseases (CVDs). Although several clinical studies have shown striking associations of TMAO levels with atherosclerosis and CVDs, TMAO determinations are not clinical routine yet. The current methodology relies on isotope-labeled internal standards, which adds to pre-analytical complexity and costs for the quantification of TMAO and its precursors carnitine, betaine or choline. Here, we report a liquid chromatography-tandem mass spectrometry based method that is fast (throughput up to 240 samples/day), consumes low sample volumes (e.g., from a finger prick), and does not require isotope-labeled standards. We circumvented the analytical problem posed by the presence of endogenous TMAO and its precursors in human plasma by using an artificial plasma matrix for calibration. We cross-validated the results obtained using an artificial matrix with those using mouse plasma matrix and demonstrated that TMAO, carnitine, betaine and choline were accurately quantified in 'real-life' human plasma samples from healthy volunteers, obtained either from a finger prick or from venous puncture. Additionally, we assessed the stability of samples stored at −20 °C and room temperature. Whereas all metabolites were stable at −20 °C, increasing concentrations of choline were determined when stored at room temperature. Our method will facilitate the establishment of TMAO as a routine clinical biomarker in hematology in order to assess the risk for CVDs development, or to monitor disease progression and intervention effects.